Adjuvant high-dose-rate brachytherapy in the management of oral cavity cancers: 5 years of experience in Iran - Kazemian, Ali; Babaei, Mohammad; Lashkari, Marzieh; Ghalehtaki, Reza; Garajei, Ata; Motiee-Langroudi, Maziar; Sebzari, Ahmadreza; Jaberi, Ramin; Gholami, Soraya; Babaloui, Somayyeh; Aghili, Mahdi (Journal of Contemporary Brachytherapy, 2017)
Purpose : Brachytherapy is a cost-effective method for the management of oral cavity cancers in low to middle income countries. We aimed to evaluate the clinical outcomes of high-dose-rate interstitial brachytherapy (HDR-IBT) in patients with oral cavity cancer. Material and methods: From 2009 to 2013, 78 patients (49 combined external beam radiotherapy [EBRT] plus IBT and 29 IBT monotherapy) with oral cavity cancers had been treated in our center. Slightly more than half the patients were male, and the median age was 54 years. The treatment was planned based on the Paris system. The main outcomes were disease-free and overall survival. Results : The median follow-up duration was 36.5 months (range, 1.17-54.23). The actuarial four-year overall and disease-free survival rates were 83% and 65%, respectively. The local and locoregional control was achieved among 89.74% and 87.17% of patients, respectively. None of the factors including tumor size, node status, gender, and radiation modality (IBT alone vs. IBT + EBRT) had a significant statistical correlation to the local control rate. All the patients tolerated the planned treatment in the IBT alone group. Late complications included a case of trismus and three cases of catheter insertion site fibrosis. Conclusions : HDR-IBT as a monotherapy or in combination with EBRT is an appropriate option for the management of oral cavity squamous cell carcinomas, and supports the improvement in treatment outcomes and toxicity profiles in adjuvant settings.